2015
DOI: 10.1074/mcp.m114.047787
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Proteins from Extinct Bison latifrons Identified by Tandem Mass Spectrometry; Hydroxylysine Glycosides are a Common Feature of Ancient Collagen

Abstract: Bone samples from several vertebrates were collected from the Ziegler Reservoir fossil site, in Snowmass Village, Colorado, and processed for proteomics analysis. The specimens come from Pleistocene megafauna Bison latifrons, dating back ϳ120,000 years. Proteomics analysis using a simplified sample preparation procedure and tandem mass spectrometry (MS/MS) was applied to obtain protein identifications. Several bioinformatics resources were used to obtain peptide identifications based on sequence homology to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 80 publications
(91 reference statements)
4
50
2
4
Order By: Relevance
“…For samples in which analysis of a separate demineralization fraction is not feasible, alternative methods that do not fractionate demineralization, or do not demineralize (e.g., Cleland & Vashishth, 2015; Hill et al, 2015), should be considered to avoid loss of identified protein diversity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For samples in which analysis of a separate demineralization fraction is not feasible, alternative methods that do not fractionate demineralization, or do not demineralize (e.g., Cleland & Vashishth, 2015; Hill et al, 2015), should be considered to avoid loss of identified protein diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Because the extant chicken bones used for these analyses were not subject to the diagenetic factors that can cause chemical alterations in fossil proteins (e.g., deamidation, carboxymethylation of lysine, loss of hydroxylations to proline (Cleland et al, 2016; Cleland, Schroeter & Schweitzer, 2015; Hill et al, 2015)), it is unclear whether the disparity of efficiencies between protocols observed here would be similar if conducted on a fossil sample. Indeed, given the chemical differences in depositional environments experienced by fossils from different localities, it is possible that similar comparison analyses of 10 different fossil specimens would yield 10 different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods for the extraction of dentin and enamel proteins has been adapted from the groups of Jàgr, Hill,and Capellini . Briefly, teeth were cut lengthwise with a diamond blade.…”
Section: Methodsmentioning
confidence: 99%
“…Liquid chromatography–tandem mass spectrometry (LC–MS/MS) has become the favorite technique to routinely identify posttranslational modifications (PTMs) of proteins of biological interest; however, a number of practical issues remain to be scrutinized for the analyses of highly modified large proteins such as collagens. 4951 Indeed, although collagen IV is very abundant, a surprising underrepresentation of sequence coverage has been observed in proteomics inventories of highly enriched BM preparations. 5256 This may be explained by the inherent properties of collagen IV such as repetitive nature of primary sequence, high insolubility, cross-linking, and resistance to cleavage due to extensive PTM, which could lead to low peptide abundance, poor primary sequence coverage, and poor identification of the location of PTMs.…”
Section: Introductionmentioning
confidence: 99%